Internationalization and SMEs: a practitioner's perspective - McDermott, Michael (Henry Stewart Talks, 2009)
Internationalization: the twin academic perspectives, The policy maker's perspective, The consultant's perspective, The challenges facing SMEs, Why begin exporting?, The 'push' and 'pull' factors, Seeking to identify priority markets, Exportitis, Identifying new markets to compensate for declining sales in the traditional markets, Addressing specific problems in markets of high strategic importance, Born global, Lack of focus